Integrated approaches to addressing drugs and development challenges in Myanmar's borderlands - Patrick Meehan (United Nations Research Institute for Social Development (UNRISD), 2022)
Policymakers have placed growing weight on the importance of integrated approaches for tackling complex development challenges. There have also been increased calls to focus attention and resources on addressing the specific challenges posed by borderland regions, considering that protracted armed conflict, chronic poverty, humanitarian emergencies, state failure, and unregulated and environmentally damaging economic activities are often concentrated in these spaces. In light of these complex and multi-faceted challenges, this paper analyses two international interventions that aimed, in different ways, to integrate drugs-related and development goals in the conflict-affected Myanmar-China borderlands. The first of these interventions is an alternative development programme implemented by the UN Office on Drugs and Crime (UNODC). This programme has sought to combine efforts to reduce opium cultivation with a wider set of rural development strategies aimed at tackling poverty, promoting gender equality, and strengthening environmental protection. The second intervention is a largescale opium substitution programme (OSP) funded by the Chinese government, which claims to tackle drug production through initiating a wider process of economic development and transformation in marginalized upland borderlands. Based on a detailed analysis of these two programmes, this paper highlights the need for integrated approaches to embed a stronger political economy analysis. It emphasizes that any kind of intervention will be shaped by power relations and competing sets of interests and must understand and be resilient to these pressures. The paper provides several key insights to guide programmes in this direction. First, integrated borderland development programmes should be underpinned by a robust and prior analysis of the context in which they are to be implemented. Second, integrated development programmes need to acknowledge, identify, and manage inherent and newly-emerging tensions and trade-offs between policy goals explicitly and honestly, rather than assuming 'all good things come together'. Finally, policymakers and practitioners need to assess the interests of different stakeholders involved in integrated programmes to determine how these interests affect the ways that programmes are designed and implemented and their outcomes.
Keywords: 330